Psychological treatment of panic - Barlow, David H.; Cerny, Jerome A. (Treatment manuals for practitioners, 1988)
A complete step-by-step manual for the cognitive-behavioral treatment of panic, this book sets forth a proven approach that therapists can readily incorporate into their existing clinical repertoire. After reviewing the etiology, nature, and assessment of panic disorder, the book guides readers through implementing and troubleshooting a treatment plan that incorporates relaxation, cognitive, and exposure components.